The Ideal Concept of Requirements for Ad Hoc Human Rights Judges at the Supreme Court to Achieve Justice - Panjaitan, Ananda Chrisna D. (Mimbar Keadilan, 2025)
Resolving severe human rights abuses in Indonesia requires serious efforts. One significant case, the human rights abuses in Paniai, remains unresolved and has not yet found justice. After the accused was acquitted, the Attorney General filed an appeal to the Supreme Court. However, the cassation process has not proceeded due to the absence of ad hoc human rights judges at the Supreme Court. The stringent requirements for ad hoc judges at the Supreme Court level serve as a barrier to attracting competent candidates. This study employs normative legal research methodology, utilizing both legislative and case approaches. The findings indicate that there is a need to amend the administrative requirements outlined in Paragraph 4, clauses (d) and (e), which pertain to the age and experience of prospective ad hoc judges. These requirements hinder qualified candidates, particularly those with expertise in severe human rights abuses, from applying. The inefficiency and ineffectiveness of these administrative criteria contribute to delays in resolving such cases. The study advocates for revising the age and experience requirements, emphasizing that the critical factor in resolving severe human rights abuses is the ad hoc judges' knowledge of victim rehabilitation and the imposition of appropriate penalties on perpetrators. Revising these requirements is essential to expedite the resolution of severe human rights abuses and to ensure a more effective judicial process.